2016
DOI: 10.1016/j.resourpol.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Does uncertainty move the gold price? New evidence from a nonparametric causality-in-quantiles test

Abstract: Much significant research has been done to study the links between gold returns and the returns of other asset classes in times of economic crisis and high uncertainty. We contribute to this research by using a novel nonparametric causality-in-quantiles test to study how measures of policy and equity-market uncertainty affect gold-price returns and volatility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(93 citation statements)
references
References 25 publications
5
87
1
Order By: Relevance
“…Interestingly, as documented by the previous studies on the same issue, we show that the different uncertainty measures display heterogenuous impacts on gold returns (for example, Blose, 2010; Jones and Sackley, 2016;Balcilar et al 2016;Beckmann et al 2017). Fig 2 (a) reports the estimate of the gold return's reaction to the macroeconomic uncertainty.…”
Section: 1the Quantile-on Quantile Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Interestingly, as documented by the previous studies on the same issue, we show that the different uncertainty measures display heterogenuous impacts on gold returns (for example, Blose, 2010; Jones and Sackley, 2016;Balcilar et al 2016;Beckmann et al 2017). Fig 2 (a) reports the estimate of the gold return's reaction to the macroeconomic uncertainty.…”
Section: 1the Quantile-on Quantile Resultssupporting
confidence: 77%
“…They showed that uncertain economic policies prompt a moderate correlation, while a strong correlation is associated with certain economic policies. Balcilar et al (2016) tested the role of economic, macroeconomic and financial uncertainty in determining gold returns and volatility, and found that macroeconomic and financial uncertainties play a vital role in explaining gold price dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, a US oil supply shock directly influences US income, 1 A considerable literature has developed examining the connection between indices of economic policy uncertainty and stock markets in various countries: Mensi et al (2014) for BRICS; Arouri and Roubaud (2016) for the US and China; Li et al (2016) for China and India; Dakhlaoui and Aloui (2016) for BRIC over time; Gao and Zhang (2016) for the UK; Wu et al (2016) for a panel of nine countries ;and Chang et al (2015) for seven OECD countries. The implications of economic policy uncertainty for sectoral returns has also been examined: Lean and Nguyen (2014) for sustainable investment returns in Asia Pacific and North America; Antonakakis et al (2016) for U.S. sustainable investments; Balcilar et al (2016) for gold returns and volatility; Kang et al (2017) global oil and gas companies. Bekiros et al (2016) argue for a non-linear forecasting connection between economic policy uncertainty stock market return volatility.…”
Section: Oil Price Shocks and Policy Uncertainty: New Evidence On Thementioning
confidence: 99%
“…The implications of economic policy uncertainty for sectoral returns has also been examined: Lean and Nguyen (2014) for sustainable investment returns in Asia Pacific and North America; Antonakakis et al (2016) for U.S. sustainable investments; Balcilar et al (2016) for gold returns and volatility; Kang et al (2017) global oil and gas companies. Bekiros et al (2016) argue for a non-linear forecasting connection between economic policy uncertainty stock market return volatility.…”
Section: Oil Price Shocks and Policy Uncertainty: New Evidence On Thementioning
confidence: 99%